The first eleven mitochondrial genomes from the ectomycorrhizal fungal genus (Boletus) reveal intron loss and gene rearrangement - Li, Qiang; Wu, Peng; Li, Lijiao; Feng, Huiyu; Tu, Wenying; Bao, Zhijie; Xiong, Chuan; Gui, Mingying; Huang, Wenli (International journal of biological macromolecules, 2021)
In the present study, eleven novel complete mitogenomes of Boletus were assembled and compared. The eleven complete mitogenomes were all composed of circular DNA molecules, with sizes ranging from 32,883 bp to 48,298 bp. The mitochondrial gene arrangement of Boletus varied greatly from other Boletales mitogenomes, and gene position reversal were observed frequently in the evolution of Boletus. Across the 15 core protein-coding genes (PCGs) tested, atp9 had the least and rps3 had the largest genetic distances among the eleven Boletus species, indicating varied evolution rates of core PCGs. In addition, the Ka/Ks value for nad3 gene was >1, suggesting that this gene was subject to possible positive selection pressure. Comparative mitogenomic analysis indicated that the intronic region was significantly correlated with the size of mitogenomes in Boletales. Two large-scale intron loss events were detected in the evolution of Boletus. Phylogenetic analyses based on a combined mitochondrial gene dataset yielded a well-supported (BPP ≥ 0.99; BS =100) phylogenetic tree for 72 Agaricomycetes, and the Boletus species had a close relationship with Paxillus. This study served as the first report on complete mitogenomes in Boletus, which will further promote investigations of the genetics, evolution and phylogeny of the Boletus genus.